Development of the international taxation system: analysis of historical stages - I.V. Orlov; D.M. Zakharov (Економіка, управління та адміністрування)
The article analyzes the historical stages of the development of the international taxation system, paying special attention to the role of transfer pricing. The evolution of rules, tools, and methods of combating aggressive tax planning, in particular transfer pricing, is considered. The analysis of changes in the approaches to erosion of the tax base and profit shifting by transnational corporations and the corresponding reactions of international organizations and national tax authorities to the prevention of transfer pricing has been carried out. The prerequisites for the emergence and effectiveness of modern approaches in combating transfer pricing, including the OERS project on the erosion of the tax base and profit shifting (BEPS) and the Two-Pillar Solution, have been studied. The article highlights the disproportion of the international taxation system with the modern challenges of the digital economy. The rapid development of digital technologies gives rise to new forms of business that are difficult to adapt to the existing tax framework. Problems related to determining the location of profits in the digital environment and calculating fair taxation for multinational corporations are becoming obstacles to achieving a balance in the international tax system. The fiscal consequences and impact on international trade and the distribution of tax revenues are analyzed. The article highlights the key trends and challenges that determine the effectiveness and sustainability of the modern international taxation system in the conditions of globalization and the digital economy.